Mediating role of information silence between destructive leadership and counterproductive work behaviour: evidence from the tanners' sector of Pakistan. (9th March 2022) - Younus, Sohail; Danish, Rizwan Qaiser; Sair, Shrafat Ali; Rahi, Samar
The purpose of this study is to examine the relationship among the destructive leadership constructs and counterproductive work behaviour (CWB) in the tanners' sector of Pakistan. Destructive leadership is composed of three constructs, which are Machiavellianism, abusive supervision, and psychopathic behaviour. The study investigated the mediating role of information silence in these relationships. The data was collected from 353 respondents by using self-administered questionnaires to the tanners' sector of Pakistan. Data were analysed through structure equation modelling and test the hypothesised relationships. Quantitative results showed the existence of destructive leadership lead to CWB in the tanners' sector. Information silence mediates the relationship among destructive leadership and CWB except the relationship of Machiavellianism with information silence and CWB. Tanneries should conduct different training sessions to reduce the effect of destructive leadership behaviour in workplace to reduce the CWB. Future studies may conduct on destructive leadership with horizontal violence and organisational politics.